The Impact of Non-Invasive Brain Stimulation on Motor Cortex Excitability and Cognition in Chronic Lower Back Pain - Corti, Emily Jean (Curtin University, 2022)
This thesis was a placebo controlled, randomised control trial that examined the impact of transcranial direct current stimulation on motor cortex excitability and cognitive function in people with chronic lower back pain. This thesis aimed to examine the potential for non-invasive brain stimulation as a therapeutic technique in the management of chronic lower back pain.